Simulation of outdoor natural ventilation for multiple workshops in industrial parks of Singapore - Thian, Wei Xiong (Nanyang Technological University, 2023)
As Singapore progressed, forested areas were cleared to make way for housing and industrial development. As such, green areas diminished, the density of concrete buildings increased, and there was a drastic change in surface coating materials. These brought about low wind velocity, and as a result, urban air temperature rose along the years. Human activities and the absorption of solar radiation on dark surfaces could lead to further overheating. The heating issue is worsened with increased use of air-conditioning to bring about living comfort, but in turn leads to additional environmental heating and carbon dioxide release. In this project, the main objective was to perform studies with aid of Computational Fluid Dynamics (CFD) simulation to investigate the airflow patterns within an industrial estate, and to find out how additional buildings would improve or affect the existing airflow. Eight CFD simulations were carried out to study the flow behaviour within the identified industrial estate. The eight studies comprise of: 1. Reference Model (North Wind) 2. Reference Model (East Wind) 3. Model 1 – Reference Model with bisected buildings (North Wind) 4. Model 1 – Reference Model with bisected buildings (East Wind) 5. Model 2 – Reference Model with new buildings (North Wind) 6. Model 2 – Reference Model with new buildings (East Wind) 7. Model 3 – Model 1 with new buildings (North Wind) 8. Model 3 – Model 1 with new buildings (East Wind) For studies 1 and 2, the reference model was replicated after a portion of Woodlands Industrial Park. The area encompassed within the reference model includes Woodlands Bus Park, Woodlands e-Terrace, Nordix, Woodlands Bus Depot, and Woodlands Lodge One. For studies 3 and 4, buildings from the reference model were bisected, with additional gaps introduced between the buildings, allowing for more even spacing between the individual buildings. For studies 5 and 6, the same layout from studies 1 and 2 was taken, while introducing new buildings into the area, which represent future building growth. For studies 7 and 8, the same layout from studies 3 and 4 was taken, while introducing the same buildings added into the area like studies 5 and 6. For all north-wind studies, the velocity inlet boundary condition is set on the northern surface, and pressure outlet boundary condition on the southern surface. Similarly, for East-wind studies, the velocity inlet boundary condition is set on the eastern surface, and pressure outlet boundary condition on the western surface.